Salivary microbiota composition before and after use of proton pump inhibitors in patients with laryngopharyngeal reflux: a self-control study - Xiaohuan Cui; Longlong Yin; Yanping Zhang; Xingwang Jiang; Lina Li; Xinxin Bi (BMC, 2024)
Abstract Background Issues associated with proton pump inhibitor (PPI) usage have been documented. PPIs affect the gastrointestinal microbiome, as well as the saliva microbiota of healthy individuals. However, the alterations in the saliva microbiota of laryngopharyngeal reflux (LPR) patients remain unclear. This study aims to examine the composition of saliva microbiota in LPR patients before and after PPI usage through a self-controlled study. Methods Thirty-two adult LPR patients participated in the study. Saliva samples were collected before and after an 8-week regimen of twice-daily administration of 20-mg esomeprazole. The impact of PPI administration on bacterial communities was assessed using 16 S rRNA gene sequencing. The functional and metabolic changes in saliva microbial communities after PPI usage were analyzed using PICRUSt2 based on our 16 S rRNA gene sequencing results. Results The alpha diversity within the salivary microbiota, as measured by the PD-whole-tree index, exhibited a significant difference between samples collected before and after PPI application (P = 0.038). Additionally, PCoA analysis of unweighted UniFrac distances (beta diversity) revealed distinct separation of saliva sample microbiota structures before and after PPI application in LPR patients, with statistical significance (Adonis test, R2 = 0.063, P< 0.010). Taxon-based analysis indicated that PPI administration increased the abundance of Epsilonproteobacteria, Campylobacterales, Campylobacteraceae, Campylobacter, and Campylobacter_gracilis, while reducing the abundance of Lactobacillaceae and Lactobacillus in salivary samples ( P< 0.050). Using LEfSe to compare bacterial abundances, Bacillaceae and Anoxybacillus were found to be enriched before PPI usage in LPR patients. Furthermore, the proportion of genes responsible for indole alkaloid biosynthesis in the salivary microbiota of LPR patients significantly increased after PPI therapy (P< 0.050). Conclusions These findings indicate that PPIs induce alterations in the salivary microbiota of LPR patients. Chinese clinical trial registry No. ChiCTR2300067507. Registered on January 10,2023 retrospectively. Level of evidence 4.